Reforming the taxation of multijurisdictional enterprises in Europe: coopetition in a bottom-up federation - Marcel Gérard (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper investigates replacing separate taxation by consolidation and formulary apportionment in a Bottom-up Federation, when a multijurisdictional firm is mobile in various respects. The reform is decided cooperatively by all the jurisdictions or by some of them, while tax rates remain within the competence of each jurisdiction. The paper sets forth the conditions for the reform to be social welfare enhancing, while not increasing tax competition. Among them, the formula should emphasize criteria that the Multijurisdictional Enterprise cannot easily manipulate and the consolidating area should protect its capacity to levy taxes by adopting a crediting system, possibly extended to accrued capital gains, vis-àvis the rest of the world. Policy conclusions are suggested accordingly.
Keywords: H32; H73; H87; 330; Unternehmensbesteuerung; Steuerreform; Multinationales Unternehmen; Theorie; EU-Staaten